PENGARUH KOMPETENSI PROFESIONAL TERHADAP KINERJA PERILAKU TENAGA PENJUAL SERTA RELEVANSINYA PADA KINERJA HASIL (STUDI KASUS PADA TENAGA PENJUAL PT DAHUA TECHNOLOGY INDONESIA) - Rhino Oktavianto; Tongam Sirait (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the effect of professional competence on sales performance outcomes through behavioral performance among salespersons at PT Dahua Technology Indonesia. The research employed a quantitative approach with a causal associative design. Data were collected from 40 salespersons using a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results indicate that professional competence has a positive and significant effect on behavioral performance, and behavioral performance has a positive and significant effect on sales performance outcomes. However, professional competence does not directly affect sales performance outcomes. The findings also confirm that behavioral performance significantly mediates the relationship between professional competence and sales performance outcomes. Therefore, professional competence can enhance performance outcomes only when it is translated into effective work behaviors such as prospecting, communication, negotiation, and relationship management. This study contributes theoretically to the development of competence-performance models in the security technology industry and provides practical implications for designing more targeted and behavior-based sales training programs.